DIMENSIONS OF ORGANIZATIONAL CULTURE (INVOLVEMENT, CONSISTENCY, ADJUSTMENT, AND MISSION) WITH NURSE WORK PRODUCTIVITY - Anas Budi; Armawati Abidin (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Nursing is one of the service providers in hospitals that is excellent, efficient, and productive. for organizational culture at RSU Labuang Makassar obtained a moderate level of involvement of 56.7%, a high level of consistency of 53.3%. The results of these studies indicate that a strong organizational culture does not show any influence in increasing organizational effectiveness. Objectives: This study aimed to determine organizational culture with the work productivity of the nurses. Methods: This research uses quantitative research with a descriptive correlation research design. Is a questionnaire, with several variables, namely involvement, adjustment, consistency, mission, and work productivity. Data analysis using correlation analysis. The research subjects were 81 nurses. Results: There is a relationship between involvement and work productivity with p-value = .001 (r = .469). There is a relationship between consistency and work productivity with p-value = .001 (r = .782). And also, there is the relationship between adjustment and work productivity with p-value = .001 (r = .820), and the relationship between mission and work productivity with p-value = .001 (r = .635). Conclusion: The relationship between organizational culture and the work productivity of nurses has a positive impact on the hospital, where organizational culture can lead nurses to be productive.